Effect of laser acupuncture on pain, range of motion, and function in patellofemoral pain syndrome: a randomised controlled trial - Allam, Nesma M.; Alsirhani, Hadeel; Alruwaili, Maani Batel; Dosh, Dalal Mabkhout; Alruwaili, Huriyyah Mislat; Almazyad, Wessal Hisham; Toson, Rokaia A.; Elimy, Doaa Ayoub; El-Sherbiny, Mohamed; Ibrahim, Ateya Megahed; Ebrahim, Hasnaa Ali; Nosseir, Nermine; et al. (Frontiers in Medicine, 2025)
BackgroundPatellofemoral pain syndrome (PFPS) is a knee disorder characterised by pain behind or surrounding the patella that predominantly affects adolescents.ObjectivesThis study aimed to evaluate the impact of laser acupuncture (LA) on pain, range of motion (ROM), and function in patients diagnosed with PFPS.Materials and methodsSixty participants, predominantly young women aged 18–25 years, were randomly distributed into two equal groups: Group A (LA group), which received laser acupuncture (LA) applied to six knee acupoints at 4 J for 80 s/point, in conjunction with an exercise programme; and Group B (Sham LA group), which received LA with the device deactivated, along with an exercise programme including stretching and strengthening exercises. Both groups underwent the intervention twice a week for 4 weeks. Pain, knee range of motion (ROM), and function were evaluated at baseline and post-treatment using the visual analogue scale (VAS), goniometer, and Kujala score, respectively.ResultsNo significant differences were observed in the VAS, ROM, and Kujala scores for knee flexion and extension between the two groups before treatment (p > 0.05). However, Group A showed a significant reduction in VAS scores (p < 0.001) and a significant improvement in the Kujala score and ROM for knee flexion and extension (p < 0.001) compared with Group B.ConclusionFour-week LA intervention combined with an exercise programme demonstrated greater improvements in pain, knee ROM, and functional ability than the exercise programme alone. However, the results cannot be generalised, as the sample was mostly composed of young women aged 18 to 25 years.Clinical trial registrationClinicalTrials.gov, identifier NCT06610981.